EMOSIONAL PADA ANAK USIA DINI (STUDI DI TK KEMALA BHAYANGKARI 01 PALEMBANG) - Salsabilla, Selly; Oktamarinda, Lidia; Rahmayanti, Indiyani; Lestari, Paramita; Muslimah, Muslimah (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
The objectives of this research are How are Social Emotional, What are the factors that cause Social Emotional Problems, How are the treatments? The research method is a case study with a qualitative descriptive approach conducted. Children with social emotional problems at kindergarten age are 4-6 years old who have non-formative behavior seen from their level of development, or adjusting both at learning time and in play activities at school or at home. The results of the study are how to handle children who have social emotional disorders, namely the opportunity to mix with people of different ages & different backgrounds, children not only communicate with words that can be understood, but also can talk about topics that are understandable and interesting to others, children have motivation to get along, guidance, reassurance, getting used to children expressing their feelings through games or stories, Parents should strengthen themselves in dealing with a social environment that is full of various human traits, children need to be introduced to criticism. Social Emotional problems are important to know for three reasons, namely seen from the interests of kindergarten children, the attitude of teachers, parents and playmates.